2018
DOI: 10.1016/j.isci.2018.11.016
|View full text |Cite
|
Sign up to set email alerts
|

Keratocytes Generate High Integrin Tension at the Trailing Edge to Mediate Rear De-adhesion during Rapid Cell Migration

Abstract: SummaryRapid cell migration requires efficient rear de-adhesion. It remains undetermined whether cells mechanically detach or biochemically disassemble integrin-mediated rear adhesion sites in highly motile cells such as keratocytes. Using molecular tension sensor, we calibrated and mapped integrin tension in migrating keratocytes. Our experiments revealed that high-level integrin tension abbreviated as HIT, in the range of 50–100 pN (piconewton) and capable of rupturing integrin-ligand bonds, is exclusively a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 41 publications
1
25
0
Order By: Relevance
“…A possible mechanism for detachment at the rear of the cell could be the mechanical disruption of integrin-ECM bonds by the actomyosin force behind the nucleus. Previous studies using keratocytes and cancer cell lines have demonstrated that actomyosin generates a traction force on focal adhesions which readily break integrin-ECM bonds (Jurchenko et al, 2014;Zhao et al, 2018). However, adhesions and stress fibers are less prominent in migrating neurons than in fibroblasts, seemingly downplaying the importance of de-adhesion at the cell posterior for neuronal migration (Jiang et al, 2015).…”
Section: Actin-myosin Based Nuclear Translocationmentioning
confidence: 99%
“…A possible mechanism for detachment at the rear of the cell could be the mechanical disruption of integrin-ECM bonds by the actomyosin force behind the nucleus. Previous studies using keratocytes and cancer cell lines have demonstrated that actomyosin generates a traction force on focal adhesions which readily break integrin-ECM bonds (Jurchenko et al, 2014;Zhao et al, 2018). However, adhesions and stress fibers are less prominent in migrating neurons than in fibroblasts, seemingly downplaying the importance of de-adhesion at the cell posterior for neuronal migration (Jiang et al, 2015).…”
Section: Actin-myosin Based Nuclear Translocationmentioning
confidence: 99%
“…However, real-time force mapping can still be achieved by recording the force map in a time-series manner and obtaining the newly produced force signal with the frame subtraction method. Figure 2 E demonstrates the real-time force in a migrating keratocyte [ 50 ]. ITSs have been applied to study cell adhesive force in keratocytes and platelets.…”
Section: Biomaterials Choices For Constructing Fluorescence Tensionmentioning
confidence: 99%
“…ITSs have been applied to study cell adhesive force in keratocytes and platelets. It was shown that high-level integrin tension (>54 pN) was generated at the cell rear margin to detach integrins off from the substrate, therefore facilitating cell rear retraction during fast cell migration [ 50 ]. ITSs also revealed the polarized force distribution in adherent platelets [ 49 ].…”
Section: Biomaterials Choices For Constructing Fluorescence Tensionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, Wang and co‐workers showed that actomyosin contraction was responsible for generating >54 pN integrin forces but not the weaker forces. In a subsequent report, Wang and co‐workers used ITS to study the magnitude and spatiotemporal dynamic of the integrin forces in migrating cells . Using keratocytes as a model system, the authors revealed that these cells generated forces >54 but <100−150 pN during rapid migration.…”
Section: Dna‐based Force Probes To Map Piconewton Forces Within Cellsmentioning
confidence: 99%